TEATRETS RUM: En analyse af scenen i Shakespeares verden - Hastrup, Kirsten (Tidsskriftet Antropologi, 1997)
Kirsten Hastrup: Theatre’s Space. An Analysis of the Stage in the World of Shakespeare In this article it is suggested that historically and structurally, Shakespeare’s theatre belongs to a liminal space, on the threshold of the city, and of order. This position makes it possible for the theatre to incorporate the contradictions of society. The stage itself is an empty space, ready to be impregnated by the imagination of both players and audience. The nature of illusion on stage is discussed, and it is argued that on stage the distinction between illusion and reality dissolves. Theatre, on the whole, is a “site of passage” where one is transported between worlds, equally real and powerful.